2017
DOI: 10.1128/jvi.00389-17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Competing HIV-1 Splice Donor Sites Uncovers a Tight Cluster of Splicing Regulatory Elements within Exon 2/2b

Abstract: The HIV-1 accessory protein Vif is essential for viral replication by counteracting the host restriction factor APOBEC3G (A3G), and balanced levels of both proteins are required for efficient viral replication. Noncoding exons 2/2b contain the Vif start codon between their alternatively used splice donors 2 and 2b (D2 and D2b). For vif mRNA, intron 1 must be removed while intron 2 must be retained. Thus, splice acceptor 1 (A1) must be activated by U1 snRNP binding to either D2 or D2b, while splicing at D2 or D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 53 publications
(77 reference statements)
2
23
0
Order By: Relevance
“…Of note, twelve effective nSNVs were clustered in SLSA1, suggesting a possible involvement of SLSA1 (sequence and/or structure) in modulation of vif production. Another important point to be mentioned in Figure 5 is that six nSNVs (V234gtg, P238ccg, K240aaa, L242ctt, A248gcg, and V249gtg) are located at distinct sites from elements reported previously ( Kammler et al, 2006 ; Exline et al, 2008 ; Mandal et al, 2009 ; Widera et al, 2013 ; Brillen et al, 2017 ). This finding suggests a potential existence of novel splicing regulatory elements so far unidentified.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Of note, twelve effective nSNVs were clustered in SLSA1, suggesting a possible involvement of SLSA1 (sequence and/or structure) in modulation of vif production. Another important point to be mentioned in Figure 5 is that six nSNVs (V234gtg, P238ccg, K240aaa, L242ctt, A248gcg, and V249gtg) are located at distinct sites from elements reported previously ( Kammler et al, 2006 ; Exline et al, 2008 ; Mandal et al, 2009 ; Widera et al, 2013 ; Brillen et al, 2017 ). This finding suggests a potential existence of novel splicing regulatory elements so far unidentified.…”
Section: Resultsmentioning
confidence: 74%
“…Numbers below the sequences represent amino acid positions of HIV-1 NL4-3 Pol-integrase. SA1/SD2 sites and reported splicing regulatory elements (ESEVif, ESE-M1, ESE-M2, G4 motif, ESS2b, ESE2b, and G I2 -1 in Kammler et al, 2006 ; Exline et al, 2008 ; Mandal et al, 2009 ; Widera et al, 2013 ; Brillen et al, 2017 ) are shown. A blue line indicates the SLSA1 region.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Designer exon splicing reporters were generated on the basis of an FGB minigene containing only neutral sequences as described before (Brillen et al 2017). Two SRSF7 binding sites were introduced by substituting the Bsu36I/NotI fragment with the PCR product using the primer pair #4705/#2620.…”
Section: Plasmidsmentioning
confidence: 99%